The Effects of Technology Innovation, Good Governance, and Organization Atmospheres on Service Performance: An Empirical Investigation of Revenue Department, Ministry of Finance - Nachairit, Ingorn; Robkob, Aukkarawit; Leemanonwarachai, Teeraporn (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
This study aims to studying the effects of technology innovation, good governance, organization atmospheres on service performance: an empirical investigation of Revenue Department, Ministry of Finance. Based on the concept of the resource-based view of the firms: RBV and Public Service Delivery Theory. From the revenue office and revenue branch office, the sampling targeted 156 sample. The study employed descriptive statistics and multiple regression analysis for hypotheses testing. The results show that technology innovation and organization atmospheres have a positive effect on high service performance of revenue officer of the revenue department. The Revenue Department should use this outcome to support innovative technology and high working encourages organization atmosphere in Revenue Department. That effect may provide better service customers of the revenue office effectively. However, Good Governance does not have a positive effect on the Revenue Performance of the Revenue Department.